Carnival and other Christian festivals : folk theology and folk performance - Harris, Max, 1949- (Joe R. and Teresa Lozano Long series in Latin American and Latino art and culture., 2003)
Publisher's description: With a riotous mix of saints and devils, street theater and dancing, and music and fireworks, Christian festivals are some of the most lively and colorful spectacles that occur in Spain and its former European and American possessions. That these folk celebrations, with roots reaching back to medieval times, remain vibrant in the high-tech culture of the twenty-first century strongly suggests that they also provide an indispensable vehicle for expressing hopes, fears, and desires that people can articulate in no other way. In this book, Max Harris explores and develops principles for understanding the folk theology underlying patronal saints' day festivals, feasts of Corpus Christi, and Carnivals through a series of vivid, first-hand accounts of these festivities throughout Spain and in Puerto Rico, Mexico, Peru, Trinidad, Bolivia, and Belgium. Paying close attention to the signs encoded in folk performances, he finds in these festivals a folk theology of social justice that--however obscured by official rhetoric, by distracting theories of archaic origin, or by the performers' own need to mask their resistance to authority--is often in articulate and complex dialogue with the power structures that surround it. This discovery sheds important new light on the meanings of religious festivals celebrated from Belgium to Peru and on the sophisticated theatrical performances they embody.